Persian trade at the Nizhny Novgorod Fair in the second half of the 19th - early 20th century and the problem of goods transporting - Gadilya Gizatullaevna Kornoukhova; Yulia Olegovna Tsareva (RUDN Journal of World History, 2021)
The article shows the role of the Nizhny Novgorod Fair as the most important point of the Russo-Persian trade in the second half of the 19th - early 20th century. The problem of transportation of goods from Persia to Nizhny Novgorod and in the opposite direction is also considered. This research is based on the body of documents stored in the Archive of Foreign Policy of the Russian Empire and introduced into scientific circulation for the first time. On the base of them the authors show the inefficiency of activity of the Caucasus and Mercury Company, which actually monopolized the goods transportation across the Caspian Sea during the revised period. The extremely low speed of delivery of Russian goods purchased by Persian merchants at the Nizhny Novgorod Fair damaged not only private merchants commerce, involved in Russian-Persian trade, but also inevitably entailed a decrease in the overall trade between the two states.